Hearts and minds : a people's history of counterinsurgency - Gurman, Hannah (New Press people's history., 2013)
Since 2006, when the U.S. Army published its new field manual on counterinsurgency (the battle for ""hearts and minds""), this guiding doctrine of the U.S. military establishment continues to command broad support from liberals and conservatives alike. The first book of its kind, Hearts and Minds retells the history of counterinsurgency from the perspective of the populations whose hearts and minds have been fought over since the end of World War II. With contributions from economists, anthropologists, social historians, and journalists, the book examines key examples of cou.